PERAN VARIABEL MEDIASI KEPUASAN PELANGGAN PADA PENGARUH IKLAN BERBASIS MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI ULANG MIE GACOAN DI YOGYAKARTA (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This study aims to analyze the influence of instagram social media-based advertising on repurchase intention with customer satisfaction as a mediating variabel. The sample in this study were 120 people with a purposive sampling technique which is part of the non-probability sampling. The method used in this study is structural analysis using variance-based aquation modeling, namely partial least squares. The result of this study : instagram social media advertising significantly effect on customer saticfaction variabel. Customer saticfaction significantly influence repurchase intention variabel. Instagram social media have no effect on repurchase intention. Customer satisfaction acts as a mediating effect of instagram social media advertising on repurchase intention.
Keywords: instagram social media-based advertising; repurchase intention; customer satisfaction.